Development of a cyclosporin A derivative with excellent anti-hepatitis C virus potency. Issue 4 (15th February 2018) - Fu, Jiping; Becker, Christopher; Cao, Li; Capparelli, Michael; Denay, Regis; Fujimoto, Roger; Gai, Yu; Gao, Zhaobo; Guenat, Christian; Karur, Subramanian; Kim, Hongyong; Li, Weikuan; et al.
Graphical abstract: Abstract: Synthetic modification of cyclosporin A at P3-P4 positions led to the discovery of NIM258, a next generation cyclophilin inhibitor with excellent anti-hepatitis C virus potency, with decreased transporter inhibition, and pharmacokinetics suitable for coadministration with other drugs. Herein is disclosed the evolution of the synthetic strategy to from the original medicinal chemistry route, designed for late diversification, to a convergent and robust development synthesis. The chiral centers in the P4 fragment were constructed by an asymmetric chelated Claisen rearrangement in the presence of quinidine as the chiral ligand. Identification of advanced crystalline intermediates enabled practical supply of key intermediates. Finally, macrocyclization was carried out at 10% weight concentration by a general and unconventional "slow release" concept.